2015
DOI: 10.1038/ejcn.2015.72
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption and all-cause mortality: a meta-analysis of cohort studies

Abstract: These results imply that fish consumption was associated with a reduced risk of all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 58 publications
3
77
1
3
Order By: Relevance
“…Although high fish consumption has been associated with reduced all-cause mortality 9 and CHD mortality risk 10 in meta-analyses of prospective studies, significant associations were not observed in the multivariate-adjusted model. Differences in fish intake may partly explain disparities in results, and SES may play an important role in mediating the association between fish intake and mortality.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although high fish consumption has been associated with reduced all-cause mortality 9 and CHD mortality risk 10 in meta-analyses of prospective studies, significant associations were not observed in the multivariate-adjusted model. Differences in fish intake may partly explain disparities in results, and SES may play an important role in mediating the association between fish intake and mortality.…”
Section: Discussionmentioning
confidence: 83%
“…26 Prospective studies have noted increased mortality risk among men and women with high total and processed red meat consumption, 7,8 whereas poultry and fish are often considered healthier substitutes for red meat. Current evidence supports the relationship between fish consumption and lower all-cause or coronary heart disease (CHD) mortality risk, 9,10 whereas the role of fish intake in cancer mortality is unclear. 1113 Findings from prospective studies relating poultry to mortality risk are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population fish intake is associated with a reduction in all-cause mortality, which has been attributed to the high content of n -3 polyunsaturated fatty acids ( n -3 PUFAs) [133]. The anti-inflammatory, anti-hyperlipidaemic and antihypertensive effects of n -3 PUFAs are well established in the general population [134]; however, there is less conclusive evidence for those patients with CKD.…”
Section: Omega-3 Polyunsaturated Fatty Acids (N-3 Pufas)mentioning
confidence: 99%
“…Whilst fish consumption is associated with a reduction in mortality outcomes in the general population [133], the evidence is less clear in CKD populations. An observational study showed that dietary fish consumption is an independent predictor of survival in haemodialysis patients [186].…”
Section: Omega-3 Polyunsaturated Fatty Acids (N-3 Pufas)mentioning
confidence: 99%
“…Fish consumption is protective against cardiovascular disease (Rimm & Mozaffarian, 2006), and all-cause mortality (Zhao et al, 2015). Omega-3 intake during pregnancy is associated with improved birth outcomes such as reduced risk of premature birth and low-birth weight ; and fish consumption throughout pregnancy and breastfeeding is associated with improved child development outcomes .…”
Section: Utilisationmentioning
confidence: 99%